PENGARUH BRAND IMAGE DAN BRAND AWARENESS TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA KONSUMEN PRODUK KECANTIKAN WARDAH DI KOTA SURABAYA - Oktavia, Yusnia; Sudarwanto, Tri (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
This study discusses how brand image, brand awareness and customer satisfaction affect customer loyalty among users of Wardah beauty products in the city of Surabaya. The purpose of this study was to test and analyze the influence of brand image and brand awareness on customer loyalty through customer satisfaction as an intervening variable for users of Wardah beauty products in Surabaya. The sampling technique used was nonprobability sampling with purposive sampling of 100 respondents who are users of Wardah beauty products in the city of Surabaya. The analytical test tool used is SPSS version 22.0 with the path analysis method. The results of this study indicate that brand image has an influence on customer satisfaction, brand awareness has an influence on customer satisfaction, brand image has an influence on customer loyalty, brand awareness has an influence on customer loyalty, and customer satisfaction has an influence on customer loyalty.